Visual evoked and event-related brain potentials in HIV-infected adults: a longitudinal study over 2.5 years - Szanyi, Jana; Kremlacek, Jan; Kubova, Zuzana; Kuba, Miroslav; Gebousky, Pavel; Kapla, Jaroslav; Szanyi, Juraj; Vit, Frantisek; Langrova, Jana (Documenta ophthalmologica. Advances in ophthalmology, 2019)
PURPOSE: The aim of this neurophysiological study was to monitor changes in the visual and cognitive function of HIV-infected patients treated with combination antiretroviral therapy. METHODS: Eleven adult Czech HIV+ patients, with a mean age of 35 years and CD4 cell count ≥ 230 × 106 cells/L of blood at the time of enrollment, underwent four to six examinations over the course of 2.5 years to evaluate pattern-reversal and motion-onset visual evoked potentials (P-VEPs and M-VEPs), visually driven oddball event-related potentials (ERPs) and Montreal Cognitive Assessments. In addition to evaluating the intraindividual change in the observed parameters, we also compared patient data to data from eleven age- and gender-matched controls. RESULTS: We did not find any significant differences in P-VEPs between the patients and controls or in the paired comparison of the first and last visit. The only significant finding for P-VEPs was a linear trend in prolongation of the 20' P-VEP P100 peak time. In M-VEPs, we found a significant intergroup difference in the N160 peak time recorded during the first visit for peripheral M-VEPs only. During the last visit, all N160 peak times for patients differed significantly from those of the control group. The only intervisit difference close to the level of significance was for peripheral M-VEPs, which confirmed the trend analysis. No significant differences between patients and controls were found in the ERPs, but the P300 peak time showed a significant difference between the first and last visits, as confirmed by the trend. Patient reaction time was not significantly delayed at the first visit; however, it was prolonged with time, as confirmed by the trend. CONCLUSION: Our aim was to evaluate whether antiretroviral treatment in HIV+ patients is sufficient to preserve brain visual function. The optic nerve and primary visual cortex function tested by the P-VEPs seem to be preserved. The prolongation of the M-VEPs suggests an individually detectable decline in CNS function, but these changes did not show a progression during the follow-up. From a longitudinal perspective, the trends in peak time prolongation of the 20' P-VEP, peripheral M-VEP, ERP and reaction time suggest a faster decline than that caused by aging in healthy populations, as previously described in a cross-sectional study.
Keywords: reakční čas; Evoked Potentials, Visual; Young Adult; Event-related potentials (ERPs); antiretrovirové látky; Motion-onset VEP; Cross-Sectional Studies; Human immunodeficiency virus (HIV); Male; zrakové evokované potenciály; zraková ostrost; Anti-Retroviral Agents; Middle Aged; longitudinální studie; Electroretinography; mladý dospělý; Motion Perception; HIV Infections; Evoked Potentials; Adult; Reaction Time; dospělí; mužské pohlaví; CD4 Lymphocyte Count; HIV infekce; Visual Acuity; evokované potenciály; Pattern-reversal VEP; počet CD4 lymfocytů; vnímání pohybu; kognice; Visual evoked potentials (VEPs); lidé; zrakové korové centrum; ženské pohlaví; Humans; průřezové studie; Visual Cortex; Longitudinal Studies; elektroretinografie; Female; lidé středního věku; Cognition